Financial Performance Analysis of SHIP Before and After the IPO Based on Liquidity, Solvency and Profitability Ratios - Riko Mersandro Permana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the financial performance of PT Sillo Maritime Perdana Tbk (SHIP) in conditions before and after the Initial Public Offering (IPO). The method used in this study is a descriptive research method with a quantitative approach, using secondary data in the form of company financial reports for 2015-2022. To measure the company's financial performance used Liquidity Ratio, Solvency Ratio and Profitability Ratio. The results of this study indicate that the liquidity and profitability of the company after the IPO is better than before the IPO, while the solvency of the company before the IPO is better than after the IPO